Анализ чувствительности и оптимизация кварцевых резонаторов - Симсон, Эдуард Альфредович; Назаренко, Сергей Александрович; Зюзин, А. Ю. (НТУ "ХПИ", 2005)
Complicated finite-element models of quartz resonators with high geometric and physical self-descriptiveness sensitivity analysis and optimization methods are given in this article. The methods have guiding to orientate on high dimensions of state and design variables. The developed mathematical apparatus application domains are examined
Keywords: колебания; резонансные частоты; матрицы жесткости; матрица Якоби; электрическое поле